WORKERS AND THE POLITICAL MOBILIZATION OF 1909- 1910. AN APPROACH TO POPULAR SOCIABILITY (Tzintzun, Revista de Estudios Históricos, 2016)
This article is about Mexico City workers as seen from formal sociability. Thechosen year represents, as everybody knows, the final crisis of the “Porfiriato” (thetime Porfirio Díaz was the President of Mexico) characterized by a political conflictand certain sectors of the society change. How some workers were inserted into theurban conflict that divided the elite is analyzed as well as their capacity to adopttheir leaders’ slogans is evaluated. The article studies the working class throughthe Mutualist and Moralizing Workers Society and the political associations thatorganized the workers during the political campaign in 1909-1910.
Keywords: Workers organization; sociability; mutualist; Moralizing Workers Society; political campaign 1910 in Mexico